1974
DOI: 10.1038/hdy.1974.86
|View full text |Cite
|
Sign up to set email alerts
|

Magnification through competition of genetic differences in yield capacity in carp

Abstract: SUMMARYTen experiments were carried out during the period 1961-69. In each experiment a pair of genetically different groups of carp was tested simultaneously for differences in growth rate in mixed ponds as well as in separate ponds. The aim of the experiments was to estimate the genetic correlation of relative growth rate under inter-group competition in mixed ponds and in the absence of intergroup competition in separate ponds. The estimate of the genetic correlation coefficient was found to be 1.0, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…For example, social interactions can affect feed intake and growth rate in domestic pigs [2,3], lead to mortality due to cannibalism in laying hens [4], result in aggression and tail biting if mixing is carried out in pigs [5], increase competition in fish [6], affect growth rate and disease traits in forestry [7-9], and result in bite marks in mink [10-13]. Because social interactions may have a heritable component, selection acting on these interactions may affect significantly response to artificial selection [14-17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, social interactions can affect feed intake and growth rate in domestic pigs [2,3], lead to mortality due to cannibalism in laying hens [4], result in aggression and tail biting if mixing is carried out in pigs [5], increase competition in fish [6], affect growth rate and disease traits in forestry [7-9], and result in bite marks in mink [10-13]. Because social interactions may have a heritable component, selection acting on these interactions may affect significantly response to artificial selection [14-17].…”
Section: Introductionmentioning
confidence: 99%
“…; 36 Moav et al ; 38 Moav & Wohlfarth ; 39 Moav & Wohlfarth ; 40 Moav & Wohlfarth ; 41 Price & Clayton ; 42 Steffens ; 43 Wohlfarth et al . ; 44 Wohlfarth et al .…”
Section: The Gxe Studies Published During 1964–2013unclassified
“…Hulata, Moav and Wohlfarth (1974, 1976) found that small differences in initial weight due to environment (age) can result in magnified differences in later growth. The size grading we performed very early was done to reduce the self‐amplifying phenotypic variance in growth that can be caused by size‐dependent competition among fish (Wohlfarth & Moav 1970; Moav & Wohlfarth 1974; Doyle & Talbot 1986; Ruzzante 1993). Fish close to the modal size were randomly chosen from each family and were used in the experiment.…”
Section: Methodsmentioning
confidence: 99%